2015
DOI: 10.1074/jbc.m115.649707
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Elevated Gene-1 (AEG-1) Contributes to Non-thyroidal Illness Syndrome (NTIS) Associated with Hepatocellular Carcinoma (HCC)

Abstract: Background: Astrocyte elevated gene-1 (AEG-1) inhibits retinoid X receptor (RXR) function and is overexpressed in human hepatocellular carcinoma (HCC), which is associated with non-thyroidal illness syndrome (NTIS). Results: AEG-1 inhibits thyroid hormone (T 3 ) function by down-regulating type I 5Ј-deiodinase (DIO1) thus contributing to NTIS. Conclusion: A novel role of AEG-1 is identified regulating cancer-associated NTIS. Significance: AEG-1 inhibition might alleviate cancer-associated debilitating disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, after grouping patients into early-intermediate (BCLC A-B) and advanced-terminal stage (BCLC C-D), the negative impact of elevated fT 4 on survival remained significant in both subgroups. Additionally, non-thyroidal illness syndrome (NTIS), characterized by low serum T 3 with normal T 4 levels, is associated with HCC and other malignancies [ 46 , 47 ]. The fact that T 3 and fT 3 levels were missing in most of our patients represents another potential bias we could not address in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, after grouping patients into early-intermediate (BCLC A-B) and advanced-terminal stage (BCLC C-D), the negative impact of elevated fT 4 on survival remained significant in both subgroups. Additionally, non-thyroidal illness syndrome (NTIS), characterized by low serum T 3 with normal T 4 levels, is associated with HCC and other malignancies [ 46 , 47 ]. The fact that T 3 and fT 3 levels were missing in most of our patients represents another potential bias we could not address in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study concurs that the expression levels of both mRNA and protein MTDH were significantly upregulated in the 20 HCC tissues compared to the matched normal adjacent tissues. MTDH contributes to HCC initiation and progression by a variety of mechanisms, such as interference with thyroid hormone (T3) function, downregulation of type I 5'-deiodinase (DIO1) level, a local hypothyroid state creation in the liver, activation of nuclear factor κB (NF-κB) and other protumorigenic signaling pathways (32). Knockdown of MTDH inhibits proliferation, invasion and notably abolishes cancer onset, growth and metastasis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The AEG-1 gene is an oncogene, which is located at chromosome 8q22 [ 5 ], and it is observed that elevated expression of AEG-1 promoted tumor proliferation, progression or metastasis in multiple carcinomas such as EC [ 6 ], HCC [ 7 ], neuroblastoma [ 8 ], breast cancer [ 9 ], prostate cancer [ 10 ] and malignant glioma [ 11 ]. In addition, AEG-1 could activate multiple molecular mechanisms to exert its functions, including nuclear factor κ-B (NF-κB) [ 12 ], phosphatidylinositol 3-kinase (PI3K)/Akt and c-Myc [ 13 , 14 ], Wnt/b-catenin [ 15 ], extracellular signal-regulated kinase (ERK) [ 7 ], activator protein 1 (AP-1) [ 10 ] and non-thyroidal illness syndrome (NTIS) [ 16 ]. Also, it was reported that AEG-1 could increase the expression of angiopoietin-1, matrix metalloprotease-2 (MMP2), hypoxia-inducible factor 1-α (HIF-α) and Tie2, which are essential in angiogenesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%